THE PARADOX OF ISLAMIC VALUES IN THE BNN HUMAN RELATIONS PROGRAM FOR ANTI-DRUG EDUCATION: Paradoks Nilai Keislaman Dalam Program Human Relations BNN Untuk Edukasi Anti-Narkoba - Sembiring, Ucok Ferry; Kholil, Syukur (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The problem of drug abuse in Binjai City, which serves as a transit city, is a serious concern for the National Narcotics Agency (BNN). The main challenge in BNN's anti-drug education program in Binjai is integrating strict Islamic values with the human relations approach, which emphasizes empathy and interpersonal support. This research aims to identify the effectiveness and challenges in implementing an Islamic-based human relations approach to raise anti-drug awareness in the Binjai community. This research uses a qualitative method with a descriptive-analytic approach, utilizing in-depth interviews with BNN employees, religious leaders, and program participants. The novelty of this research lies in the focus of the paradox between Islamic values and humanist approaches in drug rehabilitation programs that have not been widely explored. The results show that the integration of religious values and humanist approach creates an environment that supports recovery, increases participants' awareness, and reduces the stigma of drug users. However, challenges arise in aligning an empathic approach with the expectations of a society that wants a more assertive approach. This study provides a relevant and adaptive educational model for cities with similar characteristics.